2010
DOI: 10.1111/j.1743-6109.2009.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, Physiology, and Pathophysiology of Erectile Dysfunction

Abstract: Introduction Significant scientific advances during the past 3 decades have deepened our understanding of the physiology and pathophysiology of penile erection. A critical evaluation of the current state of knowledge is essential to provide perspective for future research and development of new therapies. Aim To develop an evidence-based, state-of-the-art consensus report on the anatomy, physiology, and pathophysiology of ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
342
1
30

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(396 citation statements)
references
References 331 publications
(402 reference statements)
6
342
1
30
Order By: Relevance
“…This is strongly supported by the significant correlation between the VAS scores of pain intensity and severity of SD found in the present study. Another potential contributor to interference with normal sexual function is the use of medications such as antidepressants [21,22] and opioids [18,19,20,33]. In the present study, all four classes of medications (non-opioids, opioids, antidepressants and anticonvulsants) had been used in significantly higher percentages of patients with SD than by those who did not report SD.…”
Section: Discussionmentioning
confidence: 56%
“…This is strongly supported by the significant correlation between the VAS scores of pain intensity and severity of SD found in the present study. Another potential contributor to interference with normal sexual function is the use of medications such as antidepressants [21,22] and opioids [18,19,20,33]. In the present study, all four classes of medications (non-opioids, opioids, antidepressants and anticonvulsants) had been used in significantly higher percentages of patients with SD than by those who did not report SD.…”
Section: Discussionmentioning
confidence: 56%
“…Released from endothelia and nitrergic nerves, NO stimulates soluble guanylyl cyclase in smooth muscle, promoting cGMP generation. In turn, cGMP activates cGMPdependent protein kinase (cGK) which induces smooth muscle relaxation acting on different intracellular mediators (Gratzke et al, 2010). In addition, cGMP can directly act on specific ion channels in the cell membrane also facilitating relaxation of smooth muscle (Morgado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…26 However, under experimental hyperglycemic conditions, it has been demonstrated that oxidative stress contributes to neuronal, endothelial, and smooth muscle damage in diabetic animals. 23,27,28 In addition, in diabetic men, the smooth muscle and endothelial density in the corpus cavernosum is reduced significantly.…”
Section: Discussionmentioning
confidence: 99%